Destination Marketing Strategies: Promoting Southeast Asia as a Premier Tourism Hub - Sachani, Dipakkumar Kanubhai; Vennapusa, Sai Charan Reddy (ABC Journal of Advanced Research, 2017)
This study explores destination marketing strategies to promote Southeast Asia as a premier tourism hub. The study’s main objectives are to analyze the effectiveness of current marketing approaches, identify challenges and opportunities in tourism promotion, and propose policy implications for sustainable tourism development. The methodology involves a comprehensive literature review, including academic research, industry reports, and government publications, to examine trends, best practices, and case studies in destination marketing. Significant findings highlight the region’s cultural diversity, environmental sustainability concerns, collaborative partnerships, and technological innovations as critical factors influencing tourism promotion. Policy implications underscore the importance of infrastructure development, environmental conservation, political stability, and digital transformation in fostering tourism growth and competitiveness. By addressing these challenges and leveraging opportunities, Southeast Asia can enhance its attractiveness as a premier tourism destination and stimulate economic development.